Optimizing Employee Work Quality Through Work Facilities, Training, and Leadership Style: Evidence from Gogo Fried Chicken Jimbaran - Juan Mario Radityatama; Martinus Albertian Sare Rupa (PT. Global World Scientific, 2025)
This study aims to analyze the effect of work facilities and job training on employee work quality with leadership style as a moderator variable at GOGO Fried Chicken Jimbaran branch, Badung Regency, Bali. All 12 employees were used as research respondents, so the population and research sample were the same. Data were analyzed using multiple linear regression with classical assumption tests, including normality, heteroscedasticity, and multicollinearity tests, to ensure the validity and reliability of the model. The ANOVA test results showed that the regression model was significant with a p value of 0.002, indicating that the independent variables and their interaction with leadership style simultaneously affect work quality. The results of the regression coefficient analysis show that work facilities have a significant positive effect on work quality, while job training has a significant negative effect if not accompanied by effective leadership. The interaction between work facilities and leadership style shows a negative effect, while the interaction of work training and leadership style has a significant positive effect on work quality. The coefficient of determination (R² = 0.832) indicates that 83.2% of the variation in work quality can be explained by the independent variables and their interactions. The findings confirm the importance of synergy between facilities, training and leadership in improving employee performance.